2014
DOI: 10.1002/marc.201400112
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Bending Behavior of Cross‐linked Azobenzene Liquid‐Crystalline Polymer Films with a Poly(oxyethylene) Backbone

Abstract: Cross-linked azobenzene liquid-crystalline polymer films with a poly(oxyethylene) backbone are synthesized by photoinitiated cationic copolymerization. Azobenzene moieties in the film surface toward the light source are simultaneously photoaligned during photopolymerization with unpolarized 436 nm light and thus form a splayed alignment in the whole film. The prepared films show reversible photoinduced bending behavior with opposite bending directions when different surfaces of one film face to ultraviolet lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…With increase in the proportion of methanol in MeOH/CHCl 3 , the diameter of the particles increased slowly, indicating that the HEMA units were exposed. The above results confirmed that p(HEMA‐ b ‐Azo‐IEM) has the property of an amphiphilic block polymer under visible light irradiation . Correspondently, under UV light, DLS traces indicated different morphologies of p(HEMA‐ b ‐Azo‐IEM) with increase in the proportion of methanol.…”
Section: Resultssupporting
confidence: 71%
“…With increase in the proportion of methanol in MeOH/CHCl 3 , the diameter of the particles increased slowly, indicating that the HEMA units were exposed. The above results confirmed that p(HEMA‐ b ‐Azo‐IEM) has the property of an amphiphilic block polymer under visible light irradiation . Correspondently, under UV light, DLS traces indicated different morphologies of p(HEMA‐ b ‐Azo‐IEM) with increase in the proportion of methanol.…”
Section: Resultssupporting
confidence: 71%
“…Thus, the high-speed switching of the mechanical motion (and change in the interference colour) of the crystal was achieved for both forward and backward paths by controlling the irradiation. The backward switching of this crystal occurs much faster than the bending motion of azobenzene groups reported for crystals (3.8 s) and polymer films (8 s–5 min)15192021.…”
Section: Resultsmentioning
confidence: 58%
“…To this end, photoresponsive azo-LCPs were used in our work to fabricate rectangular-shaped actuators as unit building elements. The azo-LCP actuators with parallel or splayed alignment have the ability to dynamically and reversibly transform between flat and bending states through asymmetric contraction or expansion arising from photoinduced conformation changes of azobenzene mesogens [23][24][25][26][27][28][29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%